Biomimetic strategies to engineer mineralised human tissues - Pina, S. (2015)
In the last few years, many reports have been describing promising biocompatible and biodegradable materials that can mimic in a certain extent the multidimensional hierarchical structure of bone, while are also capable of releasing bioactive agents or drugs in a controlled manner. Despite these great advances, new developments in the design and fabrication technologies are required to address the need to engineer suitable biomimetic materials in order tune cells functions, i.e. enhance cell-biomaterial interactions, and promote cell adhesion, proliferation, and differentiation ability. Scaffolds, hydrogels, fibres and composite materials are the most commonly used as biomimetics for bone tissue engineering. Dynamic systems such as bioreactors have also been attracting great deal of attention as it allows developing a wide range of novel in vitro strategies for the homogeneous coating of scaffolds and prosthesis with ceramics, and production of biomimetic constructs, prior its implantation in the body. Herein, it is overviewed the biomimetic strategies for bone tissue engineering, recent developments and future trends. Conventional and more recent processing methodologies are also described.